Physiotherapy for people with mental health problems in Sub-Saharan African countries: a systematic review - Vancampfort, Davy (Arch Physiother, 2018)
BACKGROUND: There is a need for psychosocial interventions to address the escalating mental health burden in Sub-Saharan Africa (SSA). Physiotherapists could have a central role in reducing the burden and facilitating recovery within the multidisciplinary care of people with mental health problems. The aim of this systematic review was to explore the role of physiotherapists within the current mental health policies of SSA countries and to explore the current research evidence for physiotherapy to improve functional outcomes in people with mental health problems in SSA. METHODS: The Mental Health Atlas and MiNDbank of the World Health Organization were screened for the role of physiotherapy in mental health plans. Next, we systematically searched PubMed from inception until August 1st, 2017 for relevant studies on physiotherapy interventions in people with mental health problems in SSA. The following search strategy was used: “physiotherapy” OR “physical therapy” OR “rehabilitation” AND “mental” OR “depression” OR “psychosis” OR “schizophrenia” OR “bipolar” AND the name of the country. RESULTS: The current systematic review shows that in 22 screened plans only 2 made reference to the importance of considering physiotherapy within the multidisciplinary treatment. The current evidence (N studies = 3; n participants = 94) shows that aerobic exercise might reduce depression and improve psychological quality of life, self-esteem, body image and emotional stress in people with HIV having mental health problems. In people with depression moderate to high but not light intensity aerobic exercise results in significantly less depressive symptoms (N = 1, n = 30). Finally, there is evidence for reduction in post-traumatic stress symptoms (avoidance and arousal), anxiety and depression following body awareness related exercises (N = 1, n = 26). CONCLUSIONS: Our review demonstrated that physiotherapy is still largely neglected in the mental health care systems of SSA. This is probably due to poor knowledge of the benefits of physiotherapy within mental health care by policymakers, training institutes, and other mental health care professionals in SSA. Based on the current scientific evidence, this paper recommends the adoption of physiotherapy within mental health care services and investment in research and in training of professionals in SSA.